2020
DOI: 10.1101/2020.10.07.330068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conformational Dynamics of NSP11 Peptide of SARS-CoV-2 Under Membrane Mimetics and Different Solvent Conditions

Abstract: The intrinsically disordered proteins/regions (IDPs/IDPRs) are known to be responsible for multiple cellular processes and are associated with many chronic diseases. In viruses, the existence of disordered proteome is also proven and are related with its conformational dynamics inside the host. The SARS-CoV-2 virus has a large proteome, in which, structure and functions of many proteins are not known as of yet. Previously, we have investigated the dark proteome of SARS-CoV-2. However, the disorder status of no… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The prepared LUVs were stored at 4 o C and used within seven days. Detailed protocols have been reported previously [39,41,47]. preprint (which was not certified by peer review) is the author/funder.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The prepared LUVs were stored at 4 o C and used within seven days. Detailed protocols have been reported previously [39,41,47]. preprint (which was not certified by peer review) is the author/funder.…”
Section: Methodsmentioning
confidence: 99%
“…A significant gain in negative ellipticity nearby 222 nm, and a loss of negative ellipticity around 198 nm, were observed ( Figure 10B). This type of temperature-driven structural change is known to derive from structural compaction, as observed in other disordered proteins and peptides [39,41,[43][44][45][46][47]. However, other studies on IDPs showed that disordered proteins may lose their α-helical structure with increasing temperature, suggesting that the α-helices are not solely responsible for the spectroscopic change detected by the CD spectroscopy [11].…”
Section: The E-ctd Shows a Temperature-dependent Compaction Charactermentioning
confidence: 97%
See 3 more Smart Citations